b. Reflection on medical care work in a WICHI community with photovoice methodology. - Discacciati, Vilda R.; Epstein, Daniela S.; Iñurrategui, María C.; Estremero, María J.; Reboa, Teresita F.; Rezzónico, María G. (Revista del Hospital Italiano de Buenos Aires, 2024)
The native population represents 2.38% of the total Argentine population and comprises 31 indigenous peoples distributed throughout the national territory according to the 2010 census. The University Institute of the Italian Hospital has a socio-health educational program (ISTHAT) to train professionals in social and intercultural medicine. The delegation of six professionals who participated in the program in June 2023 carried out a reflection work on the healthcare activity in a Wichi community. The specific objectives were to recognize elements of interculturality, through the photo voice methodology, and to identify through the image which aspects are valued or questioned according to the biographies and beliefs of the participants. The outstanding points were rethinking the limits of respect for another culture in scenarios of potential health risk, language as an identity element and main barrier, the view of power in the community with a gender lens, and the most violated rights basics such as access to safe water and disposal of the territory. The photographs were a valuable tool to analyze the experience on the ground within the framework of interculturality. The emerging topics were relevant and offered an opportunity to think about strategies that bring the health team closer together.
Keywords: interculturality; photovoice; qualitative research; health promotion; indigenous health; public health